Nekatera vprašanja v zvezi z izpodbijanjem dolžnikovih pravnih dejanj zunaj stečaja - Ovčak Kos, Maja (Pravnik, 2014)
A claim contesting fraudulent conveyance usually consists of two parts - claims, of both constitutive and condemnatory character. Since the statement of claim for contesting fraudulent conveyance also has a constitutive character, the authors believe that Pauliana objection needs to be invoked by means of counterclaim, which is not bound by preclusive deadlines as set in the Code of Obligations, Article 257, paragraph 1. The authors therefore advocate the fact that the deadline in case of real estate ownership transferal should be bound by the day of granting and handing over of a complete Land Register permission and not by the day of filing the proposal for Land Register entry, as is usually the view of case-law. Only granting and handing over a complete Land Register permission has the characteristics of an attempt to harm creditor as defined in the Code of Obligations, Article 255. The choice of creditor%s proper legal protection is influenced to a great extent by the manner in which the debtor has reduced its property with the intention of harming the creditor. In case of void legal transactions, challenging by means of actio Pauliana is not appropriate. If creditor succeeds in action for annulment, they cannot be denied active legitimation for action for removal of an entry in the Land Register, since in the opposite case, they could not implement such judgement and therefore, their legal protection would be ineffective.
Keywords: dolgovi; dolžniki; premoženje; prenos; upniki